Household decision-making and expenditure patterns of married men and women in Malaysia - Abdullah Yusof, Selamah; Duasa, Jarita (Springer, 2010)
This study tests two opposing models of household behavior, the income pooling hypothesis and the bargaining model, by examining the final decision-making and expenditure patterns of married men and women in Malaysia. The data used is from the responses of 1,778 married persons obtained from a survey of employed Malaysians. The results show that women are often the final decision-makers on everyday household expenditures while men make the final decisions on large household expenditures, but both men and women practice autonomy in decisions related to financial investments. In spending, variations are observed between men and women in their level and proportion of expenditure of certain categories of goods and services. Relative earning share is a significant factor in decision making as well as consumption expenditure. These results tend to support the bargaining model of household decision-making.